Current and future trends in neoadjuvant immunotherapy for the treatment of triple-negative breast cancer - de, Mello, RAB (2024)
Triple-negative breast cancer (TNBC) comprises 15–20% of all breast cancers (BC). Lacking targeted therapy options, TNBC becomes the focal point of clinical investigations aiming not only to identify drugs with enhanced response potential but also to uncover new immunological and/or metabolic pathways conducive to more effective treatments. Currently, neoadjuvant treatment for TNBC relies on standard chemotherapy in conjunction with immunotherapy, given the improved response observed with this drug combination. This review delves into the latest therapeutic updates in TNBC treatment and explores potential advancements shaping the future landscape of this disease in the neoadjuvant setting.